4-Pentenoic acid exhibits broad-spectrum antibacterial activity against foodborne pathogens by disrupting bacterial membrane integrity and inhibiting efflux pump systems - Jiaming Mu; Jie Li; Fushuang Duan; Rui Wen; Xuepeng Cai; Qingling Meng; Jun Qiao; Zhongmei Ma (International Journal of Food Microbiology, 2026)

High-accuracy estimation of global site-level soil heterotrophic respiration through Geo-XGBoost integration with expanded datasets and remote sensing - Jie Liu; Ni Huang; Luying Zhu; Jiaming Chang; Yuting Shi; Zheng Niu; Dewen Cai; Li Wang (Agricultural and Forest Meteorology, 2026)

Humic acid-mediated activation of antimony colloid during soil redox cycles: Mechanisms and environmental implications - Xiongkai Zheng; Jiaming Xu; Haiming Cai; Qiming Mo; Yihao Li; Qixian Fu; Lijuan Zeng; Yongyang Wang; Xueqin Tao; Zhi Dang; Guining Lu (Journal of Hazardous Materials, 2026)

Olfactory Valence-Processing Deficits and Aberrant Brain Network Connectivity Underlie Social Dysfunction in Shank3-/- ASD Model Mice - Dingding Yang; Qian Liu; Hangjun Ran; Teng Xue; Yifan Lu; Xiao Yang; Jiaming Wang; Ling Liu; Wenting Wang; Binbin Nie; Guohong Cai; Shengxi Wu (Neuroscience Bulletin, 2026)

In-situ sulfur element-induced heterogeneous interface engineering for high-performance supercapacitors - Mingzhe Shan; Yi Jiang; Ruixiang Xu; Bin Cai; Yi Gao; Heju Zhao; Jiaming Wang; Yaozeng Lu; Xiqing Song; Surong Tan; Yishan Yuan; Zining Li; et al. (Chemical Engineering Journal, 2026)

Identification of conserved vaccine targets in Mycoplasma bovis through integrated pan-genome and reverse vaccinology approaches with in vivo immunogenicity and safety evaluation - Jiaming Mu; Zhongmei Ma; Jie Li; Xuepeng Cai; Qingling Meng; Jun Qiao (The Veterinary Journal, 2026)

Genome-wide identification of oat EIL gene family and analysis of expression patterns under abiotic stress - Xiaodong Guo; Xuanyu Liu; Jiaming Nie; Qidi Zhang; Simeng Cai; Huiyan Liu; Bing Han; Hongbin Zhao (Genetic Resources and Crop Evolution, 2026)

Monthly Soil Respiration in China's Forests: Spatiotemporal Patterns and Drivers Over 21 Years - Jiaming Chang; Ni Huang; Li Wang; Luying Zhu; Xiaoyu Lin; Jie Liu; Zheng Niu; Dewen Cai (Global Change Biology, 2026)
Forests play a critical role as terrestrial carbon sinks in mitigating climate change. However, accurate quantification of soil respiration ( R s )—the primary CO 2 efflux from forests—remains challenging due to existing studies' overreliance on annual‐scale estimates, which obscure fine‐scale spatiotemporal dynamics and key drivers of R s . Here, we developed a 500 m resolution monthly R s dataset for China's forests (2000–2020) using remote sensing data and a geographically weighted machine learning model. A geographically weighted extreme gradient boosting model achieved the highest accuracy in predicting monthly R s ( R 2 = 0.74, RMSE = 0.8 g C m −2 day −1 ). The mean total annual R s from 2000 to 2020 was 2.32 ± 0.09 Pg C year −1 , with summer contributing most and winter least. Annual total R s and seasonal total R s showed significant increasing trends across China's forests from 2000 to 2020, with the strongest increases in southern China's young/middle‐aged natural management forests and plantations. The relationships between R s and its driving factors varied: gross primary productivity (GPP) was the primary driver of annual R s across all forest management and age classes. Seasonally, temperature dominated R s in spring/winter, and GPP dominated summer R s across all forest management and age classes, while precipitation effects varied with management/age classes and season. Our findings highlight the necessity of monthly‐scale analysis and the significant role of forest management and age in modulating R s variability.

Spatial-interaction-context and temporal-attention U-Net model for spatio-temporal prediction of Sea Surface Temperature field - Jiaming Ma; Jun Song; Junru Guo; Yanzhao Fu; Yu Cai; Yuan Zhang; Jie Tian; Ming Li (Regional Studies in Marine Science, 2025)

Porcine liver peptide ameliorates ethanol-induced liver injury via the NQO1 and ACAA1 signaling pathway through regulating oxidative stress and lipid metabolism - Zixu Wang; Lujuan Xing; Jingyu Wang; Jiaming Cai; Yuejing Hao; Ye Tao; Wangang Zhang (Food Bioscience, 2025)

Transcriptomic and metabolomic analysis reveals the effect of hydrogen sulfide on delaying fruit ripening and color transition of white fleshed strawberry (Fragaria ananassa) - Miao Sun; Yue Wen; Xuanhuan Qiao; Tao Yang; Peng Zhao; Junhao Zhao; Jiaming Luo; Jialun Zhang; Zhipeng Zhu; Weijian Cai; Meng Xu; Li Yao; et al. (Postharvest Biology and Technology, 2025)

Adipose-derived soluble fractions activated bioink promotes cutaneous repair and regeneration via mobilizing endogenous reparative cells - Wei Zhang; Jiaming Shao; Hanlei Zhou; Min Yang; Chenghao Cai; Fang He; Yiran Wang; Pengqin Xu; Sizhan Xia; Tingting Weng; Jialiang Wang; Ronghua Jin; et al. (Chemical Engineering Journal, 2025)

Digital simulation of condensation and water loss in ventilated lychee packaging - Jicheng Lin; Xiaodan Zhang; Yihong Jiang; Dongfeng Liu; Wei Cai; Guopeng Lin; Zhiwu Ding; Enli Lü; Jiaming Guo (Biosystems Engineering, 2025)

Selective expansion of TCF7-expressing tumor-reactive T cell subpopulations during ovarian tumor-infiltrating T cell production ex vivo - Dingfeng Liu; Ting Zhang; Qinli Sun; Dongli Cai; Yanan Lou; Genyu Wang; Bowen Xie; Yicheng Zhu; Chong Wang; Zhouping Lu; Chenfei Liu; Yuan Li; et al. (Science China Life Sciences, 2025)

Characterization of freshly-emitted particles from poplar wood burning: OC/EC, morphology, and elemental analysis under varying ignition temperatures - Junjie Cai; Jiaming Wu; Yingjun Chen (Atmospheric Environment, 2025)

Correction: Human Bone Marrow Mesenchymal Stem Cell–Derived Exosomes Attenuate Blood–Spinal Cord Barrier Disruption via the TIMP2/MMP Pathway After Acute Spinal Cord Injury - Wang Xin; Shi Qiang; Ding Jianing; Liang Jiaming; Lin Fangqi; Cai Bin; Chen Yuanyuan; Zhang Guowang; Xu Jianguang; Lian Xiaofeng (Molecular Neurobiology, 2025)

Effect of heat treatment on the stability of ultrasound-assisted cross-linked myofibrillar protein-stabilized emulsion filler phases via rheology and tribology - Ye Tao; Jiaming Cai; Peng Wang; Jiahui Chen; Lei Zhou; Qi Wang; Zhen Li; Jingyu Wang; Xinglian Xu (Food Hydrocolloids, 2025)

Application of rheology and interfacial rheology to investigate the emulsion stability of ultrasound-assisted cross-linked myofibrillar protein: Effects of oil phase types - Ye Tao; Jiaming Cai; Peng Wang; Jiahui Chen; Lei Zhou; Weiyi Zhang; Xinglian Xu (Food Hydrocolloids, 2024)

LSGNet: A lightweight convolutional neural network model for tomato disease identification - Shengxian Yang; Licai Zhang; Jianwu Lin; Tomislav Cernava; Jitong Cai; Renyong Pan; Jiaming Liu; Xingtian Wen; Xiaoyulong Chen; Xin Zhang (Crop Protection, 2024)

Effects and mechanisms of ultrasound-assisted emulsification treatment on the curcumin delivery and digestive properties of myofibrillar protein-carboxymethyl cellulose complex emulsion gel - Lei Zhou; Jiaming Cai; Jingyu Wang; Chao Ma; Lujuan Xing; Siah Ying Tang; Wangang Zhang (Food Research International, 2024)

Biochar reduces gaseous emissions during poultry manure composting: Evidence from the evolution of associated functional genes - Ruijing Dang; Yu Cai; Jiaming Li; Yilin Kong; Tao Jiang; Jiali Chang; Sheng Yao; Jing Yuan; Guoxue Li; Guoying Wang (Journal of Cleaner Production, 2024)

Effect of Yamadazyma triangularis derived peptide XHY69AP on muscle fatigue via regulation of AMPK/PGC-1α and Nrf2/Keap1 pathways - Jiaming Cai; Ye Tao; Lujuan Xing; Lei Zhou; Ming Ju; Wangang Zhang (Food Bioscience, 2024)

Aggregation, retention and transport of γ-MnO2 nanoparticles in water-saturated porous media: Impact on the immobility of thallium - Jiaming Luo; Dafeng Cai; Lezhang Wei; Hang Shi; Yu Liu; Haiqi Yan; Dinggui Luo; Tangfu Xiao; Xuexia Huang; Qihang Wu (Environmental Pollution, 2024)

Effects of ultrasound-assisted emulsification and carboxymethyl cellulose addition on the rheological and microstructure properties of myofibrillar protein-soybean oil emulsion gel - Lei Zhou; Dacheng Kang; Jingyu Wang; Jiaming Cai; Lujuan Xing; Wangang Zhang (Food and Bioproducts Processing, 2024)

Exploring the relationship between the interfacial properties and emulsion properties of ultrasound-assisted cross-linked myofibrillar protein - Ye Tao; Jiaming Cai; Peng Wang; Jiahui Chen; Lei Zhou; Zongyun Yang; Xinglian Xu (Food Hydrocolloids, 2024)

Identification of hepatoprotective peptides from porcine liver and its interaction with ethanol metabolizing enzymes in vitro - Zixu Wang; Lujuan Xing; Jiaming Cai; Fidel Toldrá; Yuejing Hao; Wangang Zhang (Food Bioscience, 2023)

Development of geopolymer-based composites for geothermal energy applications - Linfeng Zhang; Yingfan Wang; Boyin Ding; Jiaming Gu; Neven Ukrainczyk; Jingming Cai (Journal of Cleaner Production, 2023)

Effects of carboxymethyl cellulose on the emulsifying, gel and digestive properties of myofibrillar protein-soybean oil emulsion - Lei Zhou; Jinyuan Jiang; Fan Feng; Jingyu Wang; Jiaming Cai; Lujuan Xing; Guanghong Zhou; Wangang Zhang (Carbohydrate Polymers, 2023)

Improving the detection accuracy of the nitrogen content of fresh tea leaves by combining FT-NIR with moisture removal method - Jiaming Guo; Han Huang; Xiaolong He; Jinwei Cai; Zhixiong Zeng; Chengying Ma; Enli Lü; Qunyu Shen; Yanhua Liu (Food Chemistry, 2023)

Evaluation of intervention effects of dietary coenzyme Q10 supplementation on oxidized fish oil-induced stress response in largemouth bass Micropterus salmoides - Yuexing Zhang; Linwei Cai; Zhiyong Dong; Bowen Wu; Yangyang Gong; Baoping Zhang; Bo Wang; Jiaming Kang; Tianhong Ke; Zhijin Xu; Trond Storebakken; Bo Shi (Fish & Shellfish Immunology, 2023)

Reinforcing strategies of CFRP plate for coped steel beams against local buckling - Chi Chiu Lam; Yufei Zhang; Jiaming Gu; Jingming Cai (Engineering Structures, 2023)

The landscape of aging - Yusheng Cai; Wei Song; Jiaming Li; Ying Jing; Chuqian Liang; Liyuan Zhang; Xia Zhang; Wenhui Zhang; Beibei Liu; Yongpan An; Jingyi Li; Baixue Tang; et al. (Science China Life Sciences, 2022)

Human Bone Marrow Mesenchymal Stem Cell–Derived Exosomes Attenuate Blood–Spinal Cord Barrier Disruption via the TIMP2/MMP Pathway After Acute Spinal Cord Injury - Wang Xin; Shi Qiang; Ding Jianing; Liang Jiaming; Lin Fangqi; Cai Bin; Chen Yuanyuan; Zhang Guowang; Xu Jianguang; Lian Xiaofeng (Molecular Neurobiology, 2021)

Optimum removal conditions of aniline compounds in simulated wastewater by laccase from white-rot fungi - Bo Yang; Yacheng Wang; Zhiguo Liu; Jun Liu; Jiaming Cai (Journal of Environmental Health Science and Engineering, 2019)

Preparation of chitosan/Co-Fe-layered double hydroxides and its performance for removing 2,4-dichlorophenol - Bo Yang; Jun Liu; Zhiguo Liu; Yacheng Wang; Jiaming Cai; Lingjie Peng (Environmental Science and Pollution Research, 2019)